Islamic Capital Market Investmen In Indonesia - Irwandi, Abdurrahman (Journal of Accounting and Management, 2024)
Capital market is developed to accommodate the needs of muslims in Indonesia who want to invest capital market products in accordance with the principles of sharia. With the developing of sharia investment products in the Indonesia capital market is expected to realize the Indonesian capital market into a market that can attract investors whoare investing in accordance with Islamic teachings. In Islam investment activities can be categorized as a muamalah activity. Transactions in the capital market according to sharia law are not prohibited and allowed provided that there is no transaction that conflicts with sharia such as transactions containing elements of interest and riba and also prohibit the existence of transactions contained speculation and contain a gharar element or obscurity